Integrated Marketing Communications Program Design Of Small And Medium Enterprises For Abon Jantung Pisang Products "ibu Tintin " Using Benchmarking Approach - Dimas Langga Triandaru; Yati Rohayati; Aulia Fashanah (eProceedings of Engineering, 2015)
Abstract Ibu Tintin SME is the only SME in the area Pangalengan which makes preparations of banana, to sell products Abon Jantung Pisang need to be introduced in advance of the product advantages, Ibu Tintin has been promoting its products by following exhibitions conducted by Government Pangalengan or exhibition held by the Government of West Java, this study uses a benchmarking approach against other SMEs that have successfully promoted their products. Bechmarking in marketing communications have used another SME that has been successful, based on the results of benchmarking is done, a marketing communications tool that can be used by UKM Ibu Tintin consists of two forms, namely developing packaging designs and utilizing social media. Designed packaging consists of elements and graphic design, size and shape, the information on the packaging, and material type. The conclusion from this study is the Ibu Tintin SMEss can make improvements marketing communications and packaging and optimally utilize social media in accordance with the content that has been designed to inform the product to a new market segment, making potential customers aware of the existence of potential product offerings, increase brand awareness of consumers, influence consumer purchase decisions, and ultimately purchase products offered on an ongoing basis. Keywords: SMEs, benchmarking, marketing communications, packaging, social media